PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUKMENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPAS DI SDN 03 BENGKAYANG - Evani Emi (CV. ADIBA AISHA AMIRA, 2024)
This research aims to improve student learning outcomes by applying the discovery learning model as an alternative in solving problems. The subjects of this research were class V students at SDN 03 Bengkayang, Bengkayang District, Bengkayang Regency, consisting of 29 students. This research focuses on improving student learning outcomes. The method used is Classroom Action Research (PTK) with a discovery learning model. This research consists of two cycles, where each cycle includes planning, implementation, observation and reflection stages. Based on the research results, the percentage of achievement in the pre-cycle was 17%, cycle I reached 45%, and cycle II reached 93% in the very good category. The obstacles encountered were a lack of eflective time and materials, and the steps taken to overcome these obstacles were to examine students' activities and abilities in class in order to achieve satisfactory results. The conclusion of this research shows that the use of the discovery learning model can improve student learning outcomes. Therefore, the discovery learning model can be used as a model applied in science learning